Risk factors of local control in adrenal metastases treated by stereotactic body radiation therapy - a systematic review and meta-analysis - Liao, Xuehong; Kishi, Kazushi; Du, Kaixin; Komaki, Ritsuko; Mizoe, Junetsu; Aikawa, Gosuke; Zheng, Wei; Pan, Chao (Frontiers in Oncology, 2023)
Purpose This study is aimed to explore risk factors affect the therapy outcomes of adrenal metastases (AM) for stereotactic body radiation therapy (SBRT) and guide clinical dose selection.PubMed, Embase and Web of Science were searched in September 22, 2022 in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA). Subgroup analysis and meta-regression were used to search for sources of heterogeneity and identify risky outcomes factors. Publication bias test and sensitivity analysis were also conducted.Thirty-three studies with full text from 2009 to 2022 about AM with SBRT on 1483 patients were included. Pooled 1-and 2-year LC and overall survival(OS) were 81.7% (95% confidence interval [CI], 75.6%-86.5%) , 62.8% (95% CI, 53.8%-71.8%), 67.4% (95%CI, 61.8%-73.1%) and 46.5% (95%CI, 40.4%-52.6%), respectively. Biological effective dose (BED, ɑ/β=10) and dose per fraction affected 1-year LC (Qm=23.89, 15.10; P＜0.0001, 0.0001). In the range of 60-80Gy (BED10), the group of dose per fraction ≥ 9Gy achieved the excellent 1-year LC (< 9Gy: ≥ 9Gy =78%, 91%;  2 =10.16, P = 0.001). Tracking technology significantly affected 1-and 2-year OS (Qm = 5.73, 8.75; P = 0.017, 0.003) and high tracking adoption group showed excellent 1-and 2-year OS (78.7% [95%CI, 68.6%-88.9%]; and 62.9% [95%CI, 53.1%-72.7%]).